Effect of Forced Aeration and Turning Method on Manurial Value of Cattle, Goat and Poultry Manure Compost (Indian Journal of Animal Production and Management, 2024)
Composting is the transformation of organic  material through decomposition in to a biologically  humus rich substance suitable for growing plants.  The good management of those wastes would be  an effective means of organic matter restoration  through carbon restitution to the depleted soils  through organic amendments. A properly managed  composting process can destroy weed seeds, plant  pathogens and human pathogens. The main goal of  composting is carbon sequestration and enhances  soil quality. Compost analysis assures buyers of  bulk compost in addition to receiving good value for  their money and safe organic fertilizer. Composting  has four phases viz., mesophilic (21-45℃,  thermophilic (45-68℃), mesophilic-II (
Keywords: cattle; goat and poultry manure; forced and turning method; composting